Importance and Effectiveness of Waste Decomposer in Biodegradable and Agro-waste Management in Nepal - Devkota, Sabina; Bhattrai, Geeta; Adhikari, Parbati; Vista, Shree Prasad (NPRC Journal of Multidisciplinary Research, 2026)
Background: Agro-waste management in Nepal remains a critical concern due to existing policy gaps and weak implementation mechanisms. Although Kathmandu Metropolitan City highlighted bio-waste management in its annual policy and program (2075/76), clear and effective management approaches for the management are still lacking. Furthermore, the limited understanding of how bio-decomposers are promoted and adopted by stakeholders across the value chain still remained a concern of research. Objective: It aimed towards validifying the waste decomposers as a rapid solution for managing organic waste, while recognizing the risks associated with immature or incomplete compost, which can negatively affect soil health, plant growth, and ecosystem function Method: A qualitative case study approach was employed, using stratified purposive sampling for the selection of respondents both sellers and consumers. Since Kathmandu serves as the major hub for such products, the peripheral area of Bhaktapur and Lalitpur was included to capture the dynamics of market nodes and sub-nodes, as well as the spillover effects within the compost value chain. Results: The findings reveal gaps in awareness, quality assurance, and coordination among stakeholders involved in agro-waste management. Conclusion: By linking empirical insights with existing policy frameworks, the study identifies key areas where policy intervention is needed, particularly in promoting effective use, ensuring product quality, and strengthening institutional mechanisms. The paper concludes that improved policy alignment, enhanced stakeholder engagement, and stronger institutional support are essential for advancing sustainable and efficient bio-waste management practices in Nepal.